Peran Partai Golkar dalam Pemilu Legislatif 2014 di Padang Lawas - SYARIF HIDAYATULLAH HASIBUAN (Universitas Sumatera Utara, 2016)
Golkar Party has succeeded in gaining the most votes in the Legislative Elections in 2014 in the district Padang Lawas. The party has managed to earn a total of 20 515 vote in the election. The study describes the role of the elite GolkarParty in elections that have been held 9 April 2014 in KabupatenPadang Lawas, related to the election and the success of Golkar party has won the most votes. This study is using behavorial approach and the method isqualitative. The data collection is using interviews. The findings of this study indicate that the role of the elite of the Golkar Party is very important especially a figure Bupati Padang Lawas.He is also the chairman of the GolkarParty in Padang Lawas.Political support from the party cadres is also robust against his party.Plus there are political support of a wing of the party, such as SOKSI (Central Organization of Indonesian Independent Workers), and several community organizations, namely: IPK and LMP. Keywords: Elite, Political Parties, political support.